2018
DOI: 10.1080/09513590.2018.1441398
|View full text |Cite
|
Sign up to set email alerts
|

Overactive bladder syndrome treatment with ospemifene in menopausal patients with vulvovaginal atrophy: improvement of sexuality?

Abstract: The aim of this study was to assess the effectiveness of ospemifene in the improvement of sexual function in postmenopausal women with vulvovaginal atrophy (VVA) affected by overactive bladder syndrome (OAB) or urge urinary incontinence (UUI). One hundred five postmenopausal patients with VVA affected by OAB and/or UUI were enrolled for the study. All patients received ospemifene 60 mg for 12 weeks. Clinical examination, 3-d voiding diary and the vaginal health index (VHI) were performed at baseline and at 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…It is well known that the lower urinary tract symptom is related to female sexual function. Females with an overactive bladder and urinary incontinence had a worsened sexual life, decreased sexual desire, and loss of arousal [ 39 , 40 ]. From previous literature, estrogen supply can not only improve the symptoms of an overactive bladder and urinary incontinence but also increase sexual life [ 40 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the lower urinary tract symptom is related to female sexual function. Females with an overactive bladder and urinary incontinence had a worsened sexual life, decreased sexual desire, and loss of arousal [ 39 , 40 ]. From previous literature, estrogen supply can not only improve the symptoms of an overactive bladder and urinary incontinence but also increase sexual life [ 40 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that Ospemifene is an effective therapy after MUSs in women with MUI, improving urgency symptoms and quality of life [18]. Another study, also published by Schiavi et al, demonstrated that Ospemifene is also an effective therapy for postmenopausal women with VVA affected by OAB, improving sexual function and quality of life [19].…”
Section: Local Estrogen In the Treatment Of Oab Syndromementioning
confidence: 96%
“…37 Pain at intercourse decreases, while desire and arousal increase. 39,40 Ospemifene vs Vaginal Oestrogens: Safety VVA is a chronic and progressive disease and it would require long-term therapy. Unfortunately, adherence to treatment is weak and many women discontinue vaginal therapy for perceived inefficacy, inconvenient administration or perceived risk.…”
Section: Ospemifene An Innovative Optionmentioning
confidence: 99%